Optimization of Extraction Solvent for Analysis of Total Phenolic and Antioxidant Activity of Guava Leaves (Psidium guajava) using Simplex Centroid Design - Damarhati, Lelly Aulia; Fajriansyah, Muhamad Renza; Anyalirria; Putra, Raihan Permana; Liwanda, Novian; Nurcholis, Waras (Tropical Biopharmaca Research Center, IPB University, 2023)
Guava (Psidium guajava) is a popular tropical plant widely used as processed food and medicine for various diseases. This plant contains highly bioactive compounds like quercetin, flavonoids, and ferulic acid. The bioactive content can be influenced by the extraction method. However, the solvent used for extraction can also affect the bioactive content. Therefore, this study aims to determine the best solvent or combination of extraction solvents to extract guava leaves based on total phenolic content (TPC) and antioxidant activity using simplex centroid design (SCD). This research used guava leaf samples with various solvent combinations of water, ethanol, and acetone. The determination of phenolic content was determined using the TPC method, while the determination of antioxidants was conducted using the FRAP and ABTS methods. The research results showed that the highest TPC levels were produced by the solvent water : ethanol : acetone. Then the highest levels of FRAP and ABTS antioxidants were produced by the water: ethanol solvent. The solvent optimization solution obtained was using water: ethanol: acetone with a ratio of 0.462:0.436:0.102, respectively.